Performance and efficiency analysis of a 1600 Wp PV system: investigation of thermal, system configuration, and exergy aspects - Suwarti Suwarti; Yusuf Dewantoro Herlambang; F. Gatot Sumarno; Margana Margana; Baktiyar Mei Hermawan; Zya Jamaluddin Al Rasyid; Wisnu Dyka Pradana; Robiatul Muztaba (Jurnal Polimesin, 2026)
A hybrid photovoltaic system with a total installed capacity of 1.6 kWp, composed of monocrystalline and polycrystalline modules, was experimentally evaluated under tropical conditions. The energy storage system employs a 72V bank comprising lithium-ion and lead-acid batteries. Hourly experimental measurements were conducted, and exergy analysis based on the Second Law of Thermodynamics was applied to quantify irreversible losses. It is revealed that the system’s energy efficiency ranges from 3.33% to 8.67%. The peak efficiency occurred in the afternoon, coinciding with lower panel temperatures and greater direct power delivery. Quantitative exergy analysis further identified a maximum exergy destruction of 8486.88 W at the irradiance peak, with the lowest exergetic efficiency dropping to 3.61% due to thermal irreversibilities. Additionally, operational monitoring revealed a critical synchronization failure between the lithium Battery Management System (BMS) and the Solar Charge Controller (SCC) during low-voltage states, necessitating manual intervention for recovery. These findings highlight that thermal management and component synchronization are the primary bottlenecks for system reliability in tropical environments.